(untitled) (UNED Research Journal, 2018)
The deer Mazama temama has a wide range in the tropical rain forest of Mexico, but the IUCN classifies it as Data Deficient, and information is urgently need for management and conservation. Here we assess which population density estimation model is more appropriate among those by Tyson (1959), Mandujano and Jones (2005) and Crego and Macri (2009). We compare them with field data from Tepetla (Puebla, Mexico), from 2015 to 2017, with three replicates in the wet season and three in dry season. An ANOVA indicated that the three methods produce equivalent results.